Strategi Lobi Dan Negosiasi Divisi Humas Untuk Mencapai Kesepakatan Dalam Mendapatkan Sponsorship Pada Event Aquatrance 2023 - Hanna Renata Manalu; Lailla Nabiilah; Merlinda Sayidatina Aisyah Putri; Veiga Octa Dewi Asmara; Fionny Felisa Fernanda Kandow (Institut Nalanda, 2024)
Aquatrance 2023 is a talk show event that brings together speakers who are experts in their fields to increase knowledge related to journalism and television, build enthusiasm and creativity, expand relationships, add experience, and strengthening UPNTV's internal relationships, both the UPN Televisi Daily Management Board, the Young Generation, and the Students. New, as well as exploring more about the roles, responsibilities, challenges, and tips for becoming a presenter. This event uses funding sources in the form of sponsorship. To find sponsors, both lobbying and negotiation require a strategy so that cooperation can run well. This research aims to describe the lobbying and negotiation steps that Public Relations used at the Aquatrance 2023 event to obtain sponsors for the event. This research uses a qualitative descriptive approach using interviews as a data collection method. The data obtained by researchers is primary data. The results of this research state that the lobbying strategy implemented by the Public Relations Division of the Aquatrance 2023 event is a Direct Lobbying lobbying strategy, in the form of direct discussions with sponsors, either through WhatsApp conversations or face-to-face offline meetings and Win-Win Solution strategy negotiations to reach an agreement.